OPTIMASI CO-PROCESSING DENGAN PENGATURAN RASIO PELARUT DAN BATUBARA: STUDI BATUBARA BANKO SELATAN - Silalahi, Lambok Hilarius (Badan Pengkajian dan Penerapan Teknologi, 2009)
A liquefaction process of heavy residue and South Banko coal so-called coprocessingin order to optimize the optimum weight ratio vacuum residue (VR) tocoal is studied. Vacuum residue is co-processed with and without coal incatalyzed reaction (?-FeOOH catalyst added with sulfur) at 450oC and 8MPa(initial cold-H2 pressure) for 1 hour. All the co-processing reactions are carriedout in 5 liter stirred-batch autoclave. It is found that the co-processing produceshigher distillates and lower residue compared with using creosote oil. Upgradingof vacuum residue without coal has shown that the reactivity of vacuum residueto stimulate the distillate production. It was confirmed that there is a synergisticeffect between heavy vacuum residue and South Banko coal. It may come fromfree radical of coal fragments that possibly weak or cracking the macro-molecularstructure of heavy vacuum oil. A set of heavy vacuum residue to South Bankocoal weight-ratio is tested at 2.0, 2.5 and 3.0 for determining the effect of ratio onyield structure of the process. The distillate yield for ratio of 2.0 is higher thanother ratios. On the contrary the amount of residue produced is decreased. Thereis no significant changed on the hydrocarbon gases (C1-C4) yield when the ratiois increased from 2.0 to 2.5. A slightly decreased of C1-C4 Perolehan is observedwhen the ratio was increased to 3.0. The effect of changing ratio is not found onthe (CO+CO2) gas yield due to very small amount of oxygen content in thevacuum residue.Kata kunci: heavy vacuum residue, co-processing, south banko coal